Peningkatan Hasil Belajar Pendidikan Pancasila Dan Kewarganegaraan Peserta Didik Kelas IV B SDN IPI Melalui Model Pembelajaran Picture And Picture - Bahuddin Muh. Saleh (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
Good students’ learning outcomes can be proof that teachers have planned, and implemented learning well. A good teacher should reflect on the learning that has been done and improve it so that the learning outcomes of students increase. The purpose of this study was to determine the increasing of learning outcomes in Pancasila and Citizenship education sunject. This type of research is classroom action research, using Kemmis and Taggart designs and data collection methods using observation, tests, and interviews. The results showed that the picture and picture learning model can improve learning outcomes with an increase of 60.72%.